Comparison of Effectiveness of Two Different Doses of Propranolol on Kaposiform Hemangioendothelioma - Wei, Li; Li, Li; Xu, Zigang; Zhang, Bin; Han, Xiaofeng; Wang, Chen; Liu, Yuanxiang; Xiu, Bingyu; Qiu, Lei; Sun, Yujuan; Ma, Lin (Frontiers in Pediatrics, 2022)
Objective To compare the clinical efficacy and safety of two different doses of propranolol in the treatment of cutaneous Kaposiform hemangioendothelioma (KHE). Methods The cohort of this prospective case-control study comprised 11 children with KHE treated from October 2015 to August 2018 in our institution. All participants were clinically and pathologically diagnosed as having cutaneous KHE. The children were allocated to two groups: six children in Group A (low dose group) received oral propranolol 1.5mg/kg/d, whereas five in Group B (high dose group) received oral propranolol 2mg/kg/d. The children were checked and photographed before and after treatment. Changes in the tumors were tracked by clinical and ultrasound examination. Follow-up visits to monitor for adverse reactions occurred regularly. Results Grade I, Grade II, and Grade IV improvements in tumors were each noted in one child in Group A (three improved in total) and Grade III in two and Grade IV in another two children in Group B (four improved in total). Oral propranolol was effective in 50% and 80% of children in Groups A and B, respectively; this difference is statistically significant (P<0.01). Minor adverse reactions occurred in eight of the 11 children. Conclusions Propranolol treatment is effective against cutaneous KHE. There were no serious adverse reactions and the treatment was safe in the long term. A dose of 2mg/kg/d was more effective than 1.5mg/kg/d in the treatment of KHE and did not increase the rate of adverse reactions. Children with KHE should be treated with propranolol 2 mg/kg/d orally.